On the economics of the restructuring of world railways, with a focus on Russia - Russell W. Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2021)
This lecture, delivered at the Higher School of Economics in 2020, opens with a discussion of the modern history of economists' treatment of network industries: from cost-of-service regulation through incentive regulation to vertical restructuring. This history is then applied to the freight railways sector, followed by a discussion of the current state of the debate on rail restructuring - what we term the European versus the American model, or vertical versus horizontal separation - first generally and then in the Russian Federation. Finally, we seek to derive lessons relevant to Russia from both the empirical literature and the results of recent reform policies implemented in the United States and the European Union.
Keywords: 330; Railways; regulation; economics; competition; Russian Railways (RZhD)